Analysis of directional radiation patterns of a system of flat plane sound sources - ENGEL, Zbigniew; STRYCHNIEWICZ, Lesław (Archives of Acoustics, 1985)
This paper presents a method of determining directional radiation patterns of a system of arbitrary flat surface sound sources, source vibration velocities phase shifted by an arbitrary angle. Also the results of verification studies of this method for a system of two circular pistons are presented.